ORGANIC (C) CONTENT ANALYSIS OF (MOLE) BAMBOO SHOOTS WITH DIFFERENT EM4 DOSES: ANALISIS KANDUNGAN (C) ORGANIK DARI (MOL) REBUNG BAMBU DENGAN PEMBERIAN DOSIS EM4 YANG BERBEDA - Mizar Liyanda; Sri Agustina; Sofia Keumala Sari; Dewi Yana; Resti Yulida (PT. ROCE WISDOM ACEH, 2025)
This study aims to determine the effect of em4 dosing on the amount of carbon contained in bamboo shoot liquid organic fertilizer (LOF). This research was carried out in the laboratory of the Plantation Management Study program of the Politeknik Indonesia Venezuela and the Laboratory of the Standardization and Industrial Service Policy Agency of the Banda Aceh Industrial Service Standardization and Service Center. With 5 treatments namely M1 (without the addition of EM4), M2(with the addition of EM4 20ml), M3 (with the addition of EM4 40 ml), M4 (with the addition of EM4 60ml), M5 (with the addition of EM4 80ml). The results showed that adding EM4 did not affect bambooshoot liquid organic fertilizer ranging from temperature, pH, aroma, color, and C-organic content elements. Based on the results of further tests in the treatment of M1 (without giving EM4) M5 (giving 80 ml EM4) has different results.